2009
DOI: 10.1097/inf.0b013e31818e2aa9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Respiratory Syncytial Virus Bronchiolitis in Preterm Children Is Associated With Airway Remodeling Genes and Innate Immune Genes

Abstract: Prematurity is a risk factor for severe respiratory syncytial virus bronchiolitis. We show that genetic factors in innate immune genes (IFNA13, IFNAR2, STAT2, IL27, NFKBIA, C3, IL1RN, TLR5), in innate and adaptive immunity (IFNG), and in airway remodeling genes (ADAM33 and TGFBR1), affect disease susceptibility to a different extent in preterm children, born with underdeveloped lungs, than in term children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 14 publications
2
47
1
Order By: Relevance
“…Interferons (IFNs), produced in innate and adaptive immunity, can affect many cellular functions. Upon RSV infection, epithelial cells and infiltrating leukocytes produce type I IFNs (IFN-a/b) against the viral replication and development of disease [7]. Janssen et al [8] performed a large scale genetic association study in which they determined 347 single nucleotide polymorphisms (SNPs) in 470 children hospitalized for RSV bronchiolitis, their parents, and 1008 population controls using a candidate gene approach.…”
Section: Genetic Polymorphisms Of Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferons (IFNs), produced in innate and adaptive immunity, can affect many cellular functions. Upon RSV infection, epithelial cells and infiltrating leukocytes produce type I IFNs (IFN-a/b) against the viral replication and development of disease [7]. Janssen et al [8] performed a large scale genetic association study in which they determined 347 single nucleotide polymorphisms (SNPs) in 470 children hospitalized for RSV bronchiolitis, their parents, and 1008 population controls using a candidate gene approach.…”
Section: Genetic Polymorphisms Of Cytokinesmentioning
confidence: 99%
“…The result indicated that the SNP IFNA5 (rs10757212) demonstrated the strongest association with susceptibility to RSV bronchiolitis in children. Their current study suggested that two SNPs of IFNA13 (rs643070, c.À603G>A) and IFNAR2 (rs7279064, Phe 10 Val) only have an effect in children born at term and not in preterm children, born with underdeveloped lungs [7]. IFN-c, the only type II IFN, is an important Th1 cytokine.…”
Section: Genetic Polymorphisms Of Cytokinesmentioning
confidence: 99%
“…These data suggest that overexpression of TGF-␤ or IL-17 may promote infiltration of neutrophils, which may be involved in the development of severe RSV airway disease. Furthermore, an SNP in the receptor for TGF-␤ was found to be protective against severe RSV infection in preterm infants (55).…”
Section: Discussionmentioning
confidence: 99%
“…This included the transcriptional regulator Jun, alpha interferon (IFN-α), nitric oxide synthase, and the vitamin D receptor. The more recent study of preterm children by the same group [14] also indicated a critical association with innate immune system genes and bronchiolitis susceptibility.…”
Section: Spread Of Infectionmentioning
confidence: 91%